Impact of the TAP-like transporter in antigen presentation and phagosome maturation. (September 2019) - Lawand, Myriam; Evnouchidou, Irini; Baranek, Thomas; Montealegre, Sebastian; Tao, Sha; Drexler, Ingo; Saveanu, Loredana; Si-Tahar, Mustapha; van Endert, Peter
Highlights: No evidence for a role of TAP-L in MHC-I cross-presentation. No evidence for a role of TAP-L in endogenous MHC-II presentation. Import of long peptides into phagosomes in vitro is abolished by TAP-L deficiency. Protein and peptide degradation is enhanced in TAP-L −/− phagosomes. The principal role of TAP-L in DCs may relate to regulation of phagosome maturation. Abstract: Cross-presentation is thought to require transport of proteasome-generated peptides by the TAP transporters into MHC class I loading compartments for most antigens. However, a proteasome-dependent but TAP-independent pathway has also been described. Depletion of the pool of recycling cell surface MHC class I molecules available for loading with cross-presented peptides might partly or largely account for the critical role of TAP in cross-presentation of phagocytosed antigens. Here we examined a potential role of the homodimeric lysosomal TAP-like transporter in cross-presentation and in presentation of endogenous peptides by MHC class II molecules. We find that TAP-L is strongly recruited to dendritic cell phagosomes at a late stage, when internalized antigen and MHC class I molecules have been degraded or sorted away from phagosomes. Cross-presentation of a receptor-targeted antigen in vitro and of a phagocytosed antigen in vivo, as well as presentation of a cytosolic antigen by MHC class II molecules, is not affected by TAP-L deficiency. However, accumulation in vitro of a peptide optimally adapted to TAP-L selectivity in purified phagosomes is abolished by TAP-L deficiency. Unexpectedly, we find that TAP-L deficiency accelerates phagosome maturation, as reflected in increased Lamp2b recruitment and enhanced proteolytic degradation of phagocytosed antigen and in vitro transported peptides. Although additional experimentation will be required to definitely conclude on the role of TAP-L in transport of peptides presented by MHC class I and class II molecules, our data suggest that the principal role of TAP-L in dendritic cells may be related to regulation of phagosome maturation.